Further insights in the Tardigrada microbiome: phylogenetic position and prevalence of infection of four new Alphaproteobacteria putative endosymbionts. Issue 3 (28th November 2019) - Guidetti, Roberto; Vecchi, Matteo; Ferrari, Agnese; Newton, Irene L G; Cesari, Michele; Rebecchi, Lorena
Abstract: Data from a previous study showed that microbiomes of six tardigrade species are species-specific and distinct from associated environmental microbes. We here performed a more in-depth analyses of those data, to identify and characterize new potential symbionts. The most abundant bacterial operational taxonomic units (OTUs) found in tardigrades are classified, and their prevalence in other environments is assessed using public databases. A subset of OTUs was selected for molecular phylogenetic analyses based on their affiliation with host-associated bacterial families in tardigrades. Almost 22.6% of the most abundant OTUs found do not match any sequence at 99% identity in the IMNGS database. These novel OTUs include four putative tardigrade endosymbionts from Alphaproteobacteria (Anaplasmataceae and Candidatus Tenuibacteraceae), which are characterized by 16S rRNA gene analysis and investigated for their infection rates in: Echiniscus trisetosus, Richtersisus coronifer and Macrobiotus macrocalix . These putative endosymbionts have an infection prevalence between 9.1% and 40.0%, and are, therefore, likely secondary symbionts, not essential for tardigrade survival and reproduction. Using fluorescence in situ hybridization (FISH), we detected bacteria on the cuticle and within the ovary of E. trisetosus, suggesting possible vertical transmission. This study highlights the great contribution in biodiversity discovery that neglected phyla can provide in microbiome and symbiosis studies.